Correlation studies in safflower (Carthamus tinctorius L.): Correlation studies in safflower (Carthamus tinctorius L.) - V R GHUGE; S B GHUGE; S A SHINDE; D S SUTAR (Journal of Oilseeds Research, 2023)
Safflower (Carthamus tinctorius L.) is one of the important rabi oilseed crops. The productivity/unit area can be achieved by exploiting heterosis or by developing varieties through systematic breeding programme suitable for rainfed as well as irrigated condition. In the present study, the genotypic correlation coefficients were slightly higher than their respective phenotypic correlation coefficient for most of the character. Correlation studies indicated that plant height, days to maturity, number of effective capitulum/plant, test weight and harvest index showed significant and positive correlation with seed yield. Hence, these traits could be considered as important for improving seed yield in safflower. Hence, importance must be given to these characters because they are directly proportional to seed yield.